Lithotriptic Effect of Cinnamomum verum and Nigella sativa on Ureteric Calculi - Sanaye, Mrinal; Khan, Nikhat; Dhodi, Dinesh; Parveen, Saleha (Indian Journal of Pharmaceutical Education and Research, 2024)
Introduction Urolithiasis is one of the most prevailing diseases in the society. Conventional treatments are symptomatic and are not targeted to direct the dissolution of ureteric calculi. Thus, in this study plants like Cinnamomum verum (Lauraceae) (C. verum) and Nigella sativa (Ranunculaceae) (N. sativa) are selected to assess for their lithotriptic activity. Materials and Methods The combinations of hydroalcoholic extract of these plants were prepared (HaNsCv). Ureteric calculi of human origin were sampled from patients post lithotripsy. The sampled calculi were weighed and incubated ex vivo with various concentrations of HaNsCv extract like 50, 100, 200 and 400 mg in tris buffer (pH 7) at 37°C. The change in the size of ureteric calculi was monitored at interval of 24 hr post for a period of 9 days. Results and Discussion Amongst various concentration tested, the dissolution of ureteric calculi was initiated within 24 hr at dose 400 mg whereas remaining concentrations exhibited lithotriptic activity after 24 hr of incubation. Dissolution of ureteric calculi observed was found to be both dose dependent and time dependent. At the end on 9th day 100% dissolution of ureteric calculi was observed at dose 400 mg of HaNsCv extract. LCMS study depicted presence of flavonoids like quercetin, rutin, etc., which would have been responsible for the observed lithotriptic effect. Results obtained indicate that HaNsCv possess lithotriptic potential useful for management of urolithiasis.
Keywords: Antiurolithiatic activity; Ureteric calculi; Cinnamomum verum; Nigella sativa; ex vivo